Development of a novel sea surface temperature proxy based on bacterial 3-hydroxy fatty acids - Dong, Zhengkun; Yang, Yi; Wang, Canfa; Bendle, James A.; Ruan, Xiaoyan; Lü, Xiaoxia; Xie, Shucheng (Frontiers in Marine Science, 2023)
Gram-negative bacterial 3-hydroxy fatty acids (3-OH-FAs) have received recent attention for their potential as palaeoclimate proxies. A novel temperature proxy, the ratio of anteiso to normal C13 3-OH-FA (RAN13), has been proposed for sea surface temperature (SST) reconstruction in the North Pacific Ocean. However, whether this newly proposed temperature proxy is applicable to marginal seas with significant terrigenous input or tropical oligotrophic seas requires further investigation. Here, we analyzed the composition and distribution of 3-OH-FAs and evaluated the possible impact of various environmental parameters (SST, water depth, dissolved oxygen, salinity and nutrient concentration) on their distribution in marine surface sediments from the Bohai Sea (BS) and the South China Sea (SCS). In the BS, the potential source proxy, fractional abundance of anteiso 3-OH-FAs (average 17%), indicates 3-OH-FA geochemical signature are not greatly overprinted by terrigenous inputs. The relative abundance of long-chain 3-OH-FAs (C15-C18) are higher in the SCS (average 41%) compared to those in other seas (average 33% for all marine samples). Massive inputs of terrigenous organic matter to the BS likely result in overestimation of SSTs based on the RAN13 proxy, and limited abundance of anteiso and normal C13 3-OH-FAs in the oligotrophic SCS may increase the uncertainty of the RAN13 estimated SSTs. More importantly, we find that most short-chain 3-OH-FAs are temperature dependent, especially the fractional abundance of i-C12, a-C13, i-C14 and n-C14 with a high determination coefficient (R2 > 0.60). Based on these newly found correlations, we propose a novel proxy: RANs. The RANs index shows a strong linear relationship with SST (R2 = 0.92, p < 0.001, n = 85) and more accurate prediction than the RAN13, especially in tropical samples. Furthermore, the RANs proxy is significantly correlated with TEX86, and RANs-based SSTs are approximate to LDI derived temperature in the SCS, which support the reliability of RANs as a temperature proxy. These findings further suggest 3-OH-FA based proxies have potential for paleo-SST reconstruction, especially at higher and lower ends of the ocean temperature spectrum and even in cases where marginal inputs of terrestrial organic matter and nutrients are high.